THE INFLUENCE OF TRANSLATION TECHNIQUE ON THE QUALITY OF THE TRANSLATION OF INTERNATIONAL NEWS IN SEPUTAR INDONESIA DAILY - Akhiroh, Ninuk Sholikhah (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2013)
This descriptive qualitative research aimed to analyze and describe translation technique, and its influence on the quality of the translation of international news in Seputar Indonesia daily. The data used in this research is the document of news text in the Internasional section of daily paper, the document of source text from which the translated text was taken, informant mastering translation field, giving information about the quality of the translation, and the journalist writing of the news. This research uses a purposive sampling technique.ÃÂ Document analysis and interview were used as data collecting technique. From the analysis, it was identified the following translation techniques: Deletion, Addition, Modulation, Transposition, Established Equivalent, Particularization, Generalization, Borrowing, Reduction, Amplification,ÃÂ and Calque. ÃÂ Some techniques give positive effect on translation quality, while some others do not. The improper use of deletion and addition techniques reduce the accuracy, thus reducing the quality of the translation. The decision to use certain techniques is influenced by several factors, that is rules of journalism, the ideology of media, and media policies. The quality of the translation is described as follow: accurate for 34 (40%) translation, accurate with thematic differences for 6 (7%) translation, less accurate for 40 (46%) translation, and inaccurate for 6 (7%) translation.